Psychiatric mental health nursing concepts of care in evidence-based practice - Townsend, Mary C. 1941- (F.A. Davis Company, 2015)
Rely on the distinctive voice and dedicated vision of Mary C. Townsend to provide the most clearly written, comprehensive text for psychiatric mental health nursing. Its evidence-based, holistic approach to nursing practice focuses on both biological and behavioral components